2000
DOI: 10.1063/1.481403
|View full text |Cite
|
Sign up to set email alerts
|

Valence electron momentum spectroscopy of n-butane

Abstract: Articles you may be interested inElectron momentum spectroscopy study of Jahn-Teller effect in cyclopropane J. Chem. Phys. 130, 054302 (2009); 10.1063/1.3068619Study of the molecular structure, ionization spectrum, and electronic wave function of 1,3-butadiene using electron momentum spectroscopy and benchmark Dyson orbital theories An investigation of valence shell orbital momentum profiles of difluoromethane by binary (e,2e) spectroscopyThe valence electronic structure and momentum-space electron density dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 74 publications
(37 reference statements)
2
37
0
Order By: Relevance
“…This behavior can be experimentally observed, for example, in a system consisting of a few monolayers of Ag on a Au͑111͒ substrate, where with increasing layer thickness the quantum well states in the Ag layer resemble more and more the volume band structure. [12][13][14] A similar behavior can be found for one-dimensional systems, such as linear molecules, 15,16 e.g., linear alkanes or alkyl chains, which have been investigated with electron momentum spectroscopy 17,18 and ͑angle-resolved͒ photoelectron spectroscopy ͑͑AR͒PES͒, 9,10,15,19 which is in general a suitable technique for determining the occupied electronic band structure of a solid. [20][21][22][23][24] It was found that linear carbon chains consisting of about 17 repeat units resemble very well the intramolecular electronic band structure of polyethylene.…”
Section: Introductionmentioning
confidence: 66%
“…This behavior can be experimentally observed, for example, in a system consisting of a few monolayers of Ag on a Au͑111͒ substrate, where with increasing layer thickness the quantum well states in the Ag layer resemble more and more the volume band structure. [12][13][14] A similar behavior can be found for one-dimensional systems, such as linear molecules, 15,16 e.g., linear alkanes or alkyl chains, which have been investigated with electron momentum spectroscopy 17,18 and ͑angle-resolved͒ photoelectron spectroscopy ͑͑AR͒PES͒, 9,10,15,19 which is in general a suitable technique for determining the occupied electronic band structure of a solid. [20][21][22][23][24] It was found that linear carbon chains consisting of about 17 repeat units resemble very well the intramolecular electronic band structure of polyethylene.…”
Section: Introductionmentioning
confidence: 66%
“…4) indicates the appearance of the zigzag periodic structure with less structural defects, such as gauche ones and reduced electron-phonon coupling, at least along the alkyl chains, which is consistent with the results given above. The considerable disorder and motional freedom upon heating are expected to scatter transmitted charges, and adversely affect the 1D electronic band structure along the alkyl-chain axis, 48,91,92 a structure that facilitates transport.…”
Section: Electronic Coupling: 'Through-bond' Viewmentioning
confidence: 99%
“…Furthermore, as the energy resolution of high-resolution EMS spectrometer available is 0.52 eV, 19 the chemically most important outer valence orbital energies of n-butane could not be fully resolved by the experiment. 5 The present study therefore provides fully resolved orbital MDs for the outer valence MOs of n-butane in the region of 11-16 eV, to explore information beyond the reach of the experiment.…”
Section: Introductionmentioning
confidence: 99%